The effect of stakeholder type and non-monetary incentive on the propensity to create a budgetary slack – an experimental study among controllers - Maruszewska, Ewa Wanda; Nowak, Marta (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: This study investigated whether the type of stakeholder and the presence of non-monetary incentives affect the controller’s propensity to create budgetary slack and examines the ethical evaluation of budgetary slack creation. Methodology: The authors conducted an experiment among controllers working in Poland. Results: Both incentive and stakeholder types can influence managers’ decision-making about budgetary slack. The ethical evaluation of budgetary slack was affected by the type of stakeholder. Implications and recommendations: A negative ethical evaluation of budgetary slack does not always result in its non-acceptance, especially when the incentive is present and the stakeholder is defined by power, legitimacy, and urgency. Originality/value: Budgetary slack is not widely accepted among Polish controllers, although the needs of production workers serve as ethical justification for creating it. This study expands existing management accounting by incorporating stakeholder issues into the budgetary slack creation problem, as well as contributes to the numerous stakeholder literature, especially to the ‘accounting for stakeholders’ concept.
Argumenta Oeconomica, 2025, Nr 1 (54), s. 26-42
Keywords: budgetary slack; stakeholders; stakeholder theory; incentives; controllers; ethics